FORCE MAJEURE DURING THE COVID-19 PANDEMIC (A STUDY OF CAUSALITY IN THE PERSPECTIVE OF ENGAGEMENT LAW) - Vani Wirawan; Ariesta Wibisono Anditya; Andi Redani Suryanata; Anisah Karim (IHSA Institute, 2022)
Corona Virus Disease 2019 (COVID-19) has been declared by President Joko Widodo to be a National Disaster with Presidential Decree No. 12 of 2020 concerning the Determination of Non-Natural Disasters for the Spread of Corona Virus Disease 2019 (COVID-19) as a National Disaster, where this is the reason for delays or cancellations. In a contract related to force majeure. This study aims to analyze whether the Covid-19 pandemic cannot be said to be a force majeure that can cancel an engagement. This research contains a diagnostic form with a sociolegal or socio-legal research approach. The result of the discussion is that the Covid-19 pandemic, which has been designated as a national disaster by the Government, does not necessarily become the basis for changing or even canceling an engagement because the event is casuistic, which requires a comprehensive study and approach as well as evidence regarding the impact of the Covid-19 pandemic. This results in the parties being hindered in carrying out or fulfilling their achievements. Then, the Covid-19 pandemic, which is said to be force majeure, can only be used as the basis for a relative force majeure reason because the situation or event is only temporary, meaning that the Covid-19 pandemic as force majeure can only delay the implementation of achievements without canceling the engagement.